"Top-Down" Effects Where None Should Be Found: The El Greco Fallacy in Perception Research. (January 2014) - Firestone, Chaz; Scholl, Brian J.
A tidal wave of recent research purports to have discovered that higher-level states such as moods, action capabilities, and categorical knowledge can literally and directly affect how things look. Are these truly effects on perception, or might some instead reflect influences on judgment, memory, or response bias? Here, we exploited an infamous art-historical reasoning error (the so-called "El Greco fallacy") to demonstrate that multiple alleged top-down effects (including effects of morality on lightness perception and effects of action capabilities on spatial perception) cannot truly be effects on perception. We suggest that this error may also contaminate several other varieties of top-down effects and that this discovery has implications for debates over the continuity (or lack thereof) of perception and cognition.